Development of strategic social information seeking: Implications for cumulative culture. - Kirsten H Blakey; Eva Rafetseder; Mark Atkinson; Elizabeth Renner; Fía Cowan-Forsythe; Shivani J Sati; Christine A Caldwell (PLoS ONE)
Human learners are rarely the passive recipients of valuable social information. Rather, learners usually have to actively seek out information from a variety of potential others to determine who is in a position to provide useful information. Yet, the majority of developmental social learning paradigms do not address participants' ability to seek out information for themselves. To investigate age-related changes in children's ability to seek out appropriate social information, 3- to 8-year-olds (N = 218) were presented with a task requiring them to identify which of four possible demonstrators could provide critical information for unlocking a box. Appropriate information seeking improved significantly with age. The particularly high performance of 7- and 8-year-olds was consistent with the expectation that older children's increased metacognitive understanding would allow them to identify appropriate information sources. Appropriate social information seeking may have been overlooked as a significant cognitive challenge involved in fully benefiting from others' knowledge, potentially influencing understanding of the phylogenetic distribution of cumulative culture.